In Vitro Evaluation of Trichoderma spp. against Sugarcane Eye Spot Disease (Bipolaris sp.) - Laksamana Agadhia Raharjo; Arga Dwi Indrawan; Noni Rahmadhini (Institut Pertanian Bogor, 2024)
Sugar cane (Saccharum officinarum L.) is the main ingredient in sugar production. Sugarcane is widely cultivated in warm and tropical areas and is widely used as a sweetener because it contains a lot of fructose and glucose. National sugar production shows a decline, the majority of which is caused by pathogens, especially the fungus Bipolaris sp. capable of producing up to 85% damage per Ha if no control is applied. Biological control using Trichoderma spp. can control this pathogen and is able to promote sugarcane growth. The purpose of this study was to determine the effectiveness of Trichoderma spp. in controlling Bipolaris sp. in vitro. The results showed isolates TD1, TD2, TD3 were able to inhibit Bipolaris sp. antagonistically and volatilely, the antagonist test showed a result of 86% (TD1) while the volatile test of 65% (TD2). Conclusion Trichoderma spp. can inhibit the growth of Bipolaris sp. on an in vitro scale. Keywords: BCA, Bipolaris sp. Trichoderma spp. ABSTRAK Tebu (Saccharum officinarum L.) merupakan bahan utama dalam pembuatan gula. Tebu banyak dibudidayakan didaerah hangat dan tropikal dan banyak digunakan sebagai pemanis dikarenakan mengandung banyak fruktosa dan glukosa. Produksi gula nasional menunjukan adanya penurunan yang mayoritas disebabkan oleh patogen terutama jamur Bipolaris sp. yang mampu menghasilkan kerusakan hingga 85% per Ha jika tidak diberlakukan pengendalian. Pengendalian biologis menggunakan Trichoderma spp. dapat mengendalikan patogen ini dan mampu mendorong pertumbuhan tebu. Tujuan penelitian ini ialah untuk mengetahui efektivitas Trichoderma spp. dalam mengendalikan Bipolaris sp. secara In vitro. Hasil menunjukkan isolat TD1, TD2, TD3 mampu menghambat Bipolaris sp. secara antagonis dan volatile, uji antagonis memperlihatkan TD1 memiliki hasil 86% sementara uji volatile TD2 memiliki hasil 65%. Kesimpulan Trichoderma spp. dapat menghambat pertumbuhan Bipolaris sp. dalam skala In vitro. Kata kunci: APH, Bipolaris sp. Trichoderma spp.